2018
DOI: 10.1148/radiol.2017170845
|View full text |Cite
|
Sign up to set email alerts
|

Glioblastoma: Vascular Habitats Detected at Preoperative Dynamic Susceptibility-weighted Contrast-enhanced Perfusion MR Imaging Predict Survival

Abstract: Purpose To determine if preoperative vascular heterogeneity of glioblastoma is predictive of overall survival of patients undergoing standard-of-care treatment by using an unsupervised multiparametric perfusion-based habitat-discovery algorithm. Materials and Methods Preoperative magnetic resonance (MR) imaging including dynamic susceptibility-weighted contrast material-enhanced perfusion studies in 50 consecutive patients with glioblastoma were retrieved. Perfusion parameters of glioblastoma were analyzed and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
108
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 61 publications
(121 citation statements)
references
References 41 publications
7
108
0
2
Order By: Relevance
“…According to the study of Lemee, this region is of particular interest due the high rate of local recurrence in the peritumoral brain zone. Although DSC k t r a n s has been proven to be the most sensitive and specific predictor of brain infiltration and histological grading, recent studies also showed that DCE MRI parameters in specific areas of GBM related to the IPE are correlated with biomarkers of hypoxia and overall patient survival . This evidence supports the results obtained on the importance of the IPE habitat to the improvement of GBM patients' prognostic estimation.…”
Section: Discussionsupporting
confidence: 70%
See 4 more Smart Citations
“…According to the study of Lemee, this region is of particular interest due the high rate of local recurrence in the peritumoral brain zone. Although DSC k t r a n s has been proven to be the most sensitive and specific predictor of brain infiltration and histological grading, recent studies also showed that DCE MRI parameters in specific areas of GBM related to the IPE are correlated with biomarkers of hypoxia and overall patient survival . This evidence supports the results obtained on the importance of the IPE habitat to the improvement of GBM patients' prognostic estimation.…”
Section: Discussionsupporting
confidence: 70%
“…This methodology delineates multiparametric habitats, so called hemodynamic tissue signatures (HTSs), that share similar MRI perfusion features within the habitat. A high correlation was found between these HTS perfusion based markers and the overall survival (OS) of the patients studied . This correlation might indicate that GBM aggressiveness is associated with a high angiogenic capacity.…”
Section: Introductionmentioning
confidence: 80%
See 3 more Smart Citations